2020
DOI: 10.7150/ijbs.41867
|View full text |Cite
|
Sign up to set email alerts
|

F2r negatively regulates osteoclastogenesis through inhibiting the Akt and NFκB signaling pathways

Abstract: G-protein-coupled receptors (GPCRs) are pivotal drug targets for many diseases. Coagulation Factor II Thrombin Receptor (F2R) is an important member of GPCR family that is highly expressed in osteoclasts. However, the role of F2r in osteoclasts is still unclear. Here, to examine the functions of F2r on osteoclast formation, differentiation, activation, survival, and acidification, we employed loss-of-function and gain-of-function approaches to study F2r using F2r-targeted short hairpin RNA (sh-F2r) lentivirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The total RNA was extracted from primary monocytes or osteoclasts induced for 3 days or 5 days with TRIzol reagent (Invitrogen Corp., Carlsbad, CA) reagent according to the manufacturer's protocol to perform RNA-sequence analysis. These RNA samples were sequenced on an Illumina HiSeq 2000 system (Illumina, San Diego, CA) 30 to obtain 100 base-pair single-end reads per sample 31 . The modified results can be imported to Heatmapper web server to visualize the Heat map 32 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total RNA was extracted from primary monocytes or osteoclasts induced for 3 days or 5 days with TRIzol reagent (Invitrogen Corp., Carlsbad, CA) reagent according to the manufacturer's protocol to perform RNA-sequence analysis. These RNA samples were sequenced on an Illumina HiSeq 2000 system (Illumina, San Diego, CA) 30 to obtain 100 base-pair single-end reads per sample 31 . The modified results can be imported to Heatmapper web server to visualize the Heat map 32 .…”
Section: Methodsmentioning
confidence: 99%
“…The total RNA was reverse transcribed into cDNA using RevertAid RT Kit (K1691, Thermo Scientific) according to the manufacturer's instructions. We carried out qPCRs by using SYBR Green Reagents (4309155, Thermo Scientific) and Step-One Real-Time PCR System (Life Technologies, Applied Biosystems) 30 , 33 . The expression of glyceraldehyde-3-phosphate dehydrogenase ( Gapdh ) was used as an endogenous control for normalization.…”
Section: Methodsmentioning
confidence: 99%
“…Absent levels or defective function of either FVIII or FIX impairs FX activation resulting in deficient thrombin generation. Both osteoblasts and osteoclasts express the thrombin receptor (F2R or PAR1) [10,[27][28][29], and in vitro studies indicate that thrombin induces differentiation of osteoblasts [29][30][31][32] and negatively regulates osteoclast formation and function [33,34]. In support of this mechanistic hypothesis, Aronovitch et al [35] demonstrated complete knockout of either FVIII or PAR1 in mice resulted in similar bone structural abnormalities.…”
Section: Discussionmentioning
confidence: 97%
“…Complex signaling pathways are involved in osteoclast formation and function. The binding of RANKL to RANK in osteoclast precursor cells results activation of osteoclast through signaling cascades including NFκBp65, MAPKs (ERK, JNK, and p38MAPK), and AKT pathways (31,32). Osteoprotegerin (OPG) prevents RANKL binding to RANK and inhibits bone resorption (33).…”
Section: Discussionmentioning
confidence: 99%